Sistem Informasi Bel Sekolah Otomatis dengan Fitur Penjadwalan Dinamis Menggunakan Teknologi Mikrokontroler - Pasaribu, Sutrisno Arianto; Pasaribu, Victor Patar; Rozy, Ahmad; Wijaya, Vera; Sari, Suci Amalia (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
There are many innovations made to help students learn better due to advances in educational technology. One innovation is an automatic school bell application that has dynamic scheduling. This application aims to replace the manual bell system which often requires direct intervention from officers. With dynamic scheduling, schools can easily set schedules according to their needs, be it regular schedules or special schedules such as exams or other activities. The focus of this research is the design and development of an automatic school bell application that supports automatic bell time settings. With the dynamic scheduling feature, this system allows users to change or adjust the bell schedule without disrupting the lesson schedule or other important times. The implementation results show that this application works well and allows easy bell schedule settings and improves operational efficiency in the school environment. In addition, users will receive automatic notifications about schedule changes, which reduces errors or delays in ringing the bell. This application is expected to be a solution for schools that want to improve their time management and increase their operational efficiency.